2015
DOI: 10.1039/c5ta01273b
|View full text |Cite
|
Sign up to set email alerts
|

Ruddlesden Popper oxides of LnSr3Fe3O10−δ (Ln = La, Pr, Nd, Sm, Eu, and Gd) as active cathodes for low temperature solid oxide fuel cells

Abstract: PrSr3Fe3O10−δ, Ruddlesden Popper type oxide, is highly promising as a cathode for low temperature SOFCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Small peaks corresponding to impurity phase, mainly the (EuSr)FeO 3 and (EuSr) 2 FeO 4 impurities, can be detected in Co‐content samples, especially in x =1.0 and 1.5 samples, which might be formed due to slight decomposition from three‐layer down to two‐ or one‐layer. Similar results were also detected in some other reports . It can be concluded that more Co dopant could lead to structural instability in thermal stability testing.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Small peaks corresponding to impurity phase, mainly the (EuSr)FeO 3 and (EuSr) 2 FeO 4 impurities, can be detected in Co‐content samples, especially in x =1.0 and 1.5 samples, which might be formed due to slight decomposition from three‐layer down to two‐ or one‐layer. Similar results were also detected in some other reports . It can be concluded that more Co dopant could lead to structural instability in thermal stability testing.…”
Section: Resultssupporting
confidence: 91%
“…The substitution of lanthanides at the A site not only stabilizes the R−P structure but also improves the electrical property of materials . Ishihara and co‐workers have reported a potential candidate in the series of LnSr 3 Fe 3 O 10− δ (Ln=La, Pr, Nd, Sm, Eu, Gd) with La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3 (LSGM) electrolyte and EuSr 3 Fe 3 O 10− δ shows the lowest thermal expansion coefficient (16.1×10 −6 K −1 ) . In our previous work, we demonstrated that the substitution of Eu 3+ in Sr 3 Fe 2 O 7− δ (SrEu 2 Fe 2 O 7− δ ) can effectively depress the basicity at the expense of oxygen vacancy concentration, which helps to improve the chemical stability in Lewis acid‐involved (e. g., steam and CO 2 ) atmosphere .…”
Section: Introductionmentioning
confidence: 99%
“…It is widespread that reversible intercalation and diffusion of oxide anion into the perfectly ordered structure (structure containing no oxygen vacancy) is quite difficult due to their relatively large size. Recently, perovskite-structure (ABO 3 ) and its other derivatives such as double perovskite oxides (AA 0 BB 0 O 6 ) 12 and Ruddlesden-Popper perovskites {(AO)(ABO 3 ) n } 13 have received great attention in supercapacitor field because of its ability to contain a large number of oxygen vacancies in its structure. In 2014, Mefford et al reported anion-intercalation type pseudocapacitance for LaMnO 3 perovskite in which oxygen-vacancy mediated redox has been applied for fast charge storage.…”
Section: Introductionmentioning
confidence: 99%
“…The formula can also be written as AO­(ABO 3 ) n , where the A site is usually occupied by a rare earth element, or an alkaline earth metal element, or by mixed rare earth and alkaline earth elements, while the B site is normally a transition metal element, i.e., Ni, Mn, Cu, Fe, etc., for most of the RP or RP-related structural materials that had been reported. These typical RP-structured materials with B site as transition metals have been extensively studied as potential electrode materials for SOFCs due to their excellent oxygen reduction reaction (ORR) activity, long-term stability, and chemical stability besides their high mixed oxide ion and electronic conductivities . However, for RP-structured materials with the B site being an indium element, cases have been reported only for NdBaInO 4 and Ln 2 BaIn 2 O 7 (Ln = La and Nd), which have stoichiometric oxygen content, although there are also several special cases, e.g., (Ba, Sr) 3 In 2 O 6 , , which are isotypic to the La 2 SrCu 2 O 6 material and can be viewed as derivates of the RP family, forming double pyramidal but not octahedral indium layers on account of their intrinsic severe oxygen deficiency, intergrowth with single rock salt layers.…”
Section: Introductionmentioning
confidence: 99%